2015
DOI: 10.1108/mrr-05-2014-0099
|View full text |Cite
|
Sign up to set email alerts
|

The impact of demographic factors on the way lesbian and gay employees manage their sexual orientation at work

Abstract: Original Citation: Köllen, Thomas (2015) The impact of demographic factors on the way lesbian and gay employees manage their sexual orientation at work: An intersectional perspective. Management Research Review, 38 (9). pp. 992-1015992- . ISSN 2040 This version is available at: http://epub.wu.ac.at/4654/ Available in ePub WU : September 2015 ePub WU , the institutional repository of the WU Vienna University of Economics and Business, is provided by the University Library and the IT-Services. The aim is to ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 118 publications
(167 reference statements)
0
4
0
Order By: Relevance
“…According to King et al (2017), the use of revealing strategies (implicitly and explicitly out) is more likely to occur when interacting with other LGB people and with people who indicate acceptance of LGB people. Köllen (2015) studied demographic factors for the application of identity management strategies at work. As in the study by Frohn et al (2017), the relationship status of the employee was found to be an important factor, because employees who are in a permanent relationship tend to be "Explicitly Out."…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…According to King et al (2017), the use of revealing strategies (implicitly and explicitly out) is more likely to occur when interacting with other LGB people and with people who indicate acceptance of LGB people. Köllen (2015) studied demographic factors for the application of identity management strategies at work. As in the study by Frohn et al (2017), the relationship status of the employee was found to be an important factor, because employees who are in a permanent relationship tend to be "Explicitly Out."…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In this study, the authors adopt the older but narrower term describing sexual orientation – LGBT – for employees, as it is the most frequently considered collective group in workplace diversity research (Köllen, 2013, 2015), despite an acknowledgment of the complexity of first hand experiences (McCall, 2005) and the extended modern identification continua (Killerman, 2013; Paisley and Tayar, 2016). LGBT employees are still an “invisible” but fairly large minority group (Gonsiorek and Weinrich, 1991; Ragins, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…They may apply a number of strategies how to manage their identity in the workplace (Chung, 2001; Ozeren and Aslan, 2016). The decision to come out at work is related to worker's demographic characteristics, personality traits as well as contextual factors such as organizational climate or policies (Chaudoir and Fisher, 2010; Fric, 2019; Jones and King, 2013; Köllen, 2015; Meinhold and Frohn, 2016; Wax et al , 2018). The literature often links disclosure of homosexual orientation with positive psychological outcomes such as increased job satisfaction or lower levels of anxiety and depression (Drydakis, 2015; Griffith and Hebl, 2002; Legate et al , 2012; Mohr et al , 2019).…”
Section: Introductionmentioning
confidence: 99%